PENGARUH PERSEPSI NILAI DAN ELECTRONIC WORD OF MOUTH TERHADAP INTENSI MENONTON FILM LOKAL DI BIOSKOP MELALUI MEDIASI SIKAP - Regina Deka Sofia (POLITEKNIK LP3I JAKARTA, 2025)
The objective of this study is to examine the impact of perceived value and electronic word of mouth on the intention to watch local films in cinemas, both directly and through attitude mediation. A survey-based data collection approach was employed, utilizing a questionnaire administered to 437 respondents in the city of Banten, Tangerang. The data were analyzed using Multiple Regression Analysis and the PROCESS Mediation Test. The findings indicate a positive effect of perceived value, both directly and indirectly through attitude mediation, on the intention to watch local films in cinemas. Additionally, the study reveals that the effect of electronic word of mouth on the intention to watch local films in cinemas is fully mediated by attitude. This research offers managerial insights, suggesting that marketers and stakeholders within the Indonesian film industry should develop marketing strategies that enhance consumers' perceptions of value and foster positive attitudes toward the behavior of watching local films in cinemas.